Clinical Characteristics of Cases with Spinal Muscular Atrophy - Mehmet Canpolat; Hüseyin Per; Munis Dundar (Güncel Pediatri)
Introduction: The aim of this study is was to evaluate the clinical features of cases with diagnosis of spinal muscular atrophy (SMA). Materials and Methods: Thirty-eight pediatric patients were evaluated retrospectively. All patients were followed in the Pediatric Neurology Department of Erciyes University Faculty of Medicine. The diagnosis of patients had been confirmed by genetic analysis of homozygous deletions of survival motor neuron 1 gene. Detailed history, newborn symptoms, nutritional characteristics, initial complaints, physical examination, concomitant pathologies, genetic characteristics, and treatment modalities were investigated in all patients. Results: The study population consisted of 19 boys (50%) and 19 girls (50%). The mean age of patients was 26.9±25.7 months (range: 3-96 months). The mean follow-up period was 12.2±13.3 months (range: 2-48 months). According to SMA classification, 22 patients (57.8%) were type 1, 8 patients (21.1%) were type 2, and 8 patients were (21.1%) type 3. Neonatal respiratory distress, age at early diagnosis, nutritional problems, and recurrent lung diseases were detected as poor prognostic factors. Conclusions: SMA is a neuromuscular disease that requires multidisciplinary approach to medical care. There is a wide range of clinical severity. Identification of poor prognostic factors will help in terms of guiding close monitoring and timely treatments of children with SMA.